(3GdQSGdI GdhGRYI ddeYJOjf Yf SH CUMGH SjO GdeQSdjfs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPi ChVM dfG efGQ GdHQgGf CeG HYO aMb Ydi ef efMg Gddg ai GdYde HUjQI Cf jchf geg GdPH Yf LhRI GdOjf s
(3BNQgG (B:s
(3hbO SCdfG Gddg dce Cf jTQM UOhQce dEJHGY GdMb heYQaJg hCf jgOjfG hEjGce deG jMH hjQVi s
(3CLGH HgG Ydi eSGFd hQOJ ef YHO Gddg Hf eSYhO GdPgdis
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ GdahGJM HGdSejc s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
Keywords: (3Gdabg GdESdGejs